DAN SURAT KABAR PUN BERASAP (MEMAKNAI PESAN VISUAL HARIAN REPUBLIKA EDISI KAMIS 8 OKTOBER 2015) - Anita Trisiah (Wardah, 2015)
Smoke had been familiar recently in Indonesia. It was caused by the burning of forest both consciously and unconsciously. And, the effect of this situation was very dangerous for every citizens especially those who lived in the area. Government, local and national, give no worthy respond toward the problem until a national newspaper made a breakthrough by making an extraordinary layout on it first page, a smoky page. This lead people asked question on what it meant. Through the semiotic theory stated by Roland Barthes, the researcher tried to find out what it meant denotatively and connotatively through some stages, signifier, signified and sign. After analyzing the stages, it was found that the smoky front page contained many messages. But, the main point was the illustration of what citizen who lived in the smoky city felt. Moreover, important news was not seen clearly.